Recent Progress in Electromagnetic Production of Associated Strangeness on the Nucleon - Terry Mart (Institut Teknologi Bandung, 2007)
We discuss recent developments in electromagnetic production of kaon of a nucleon. A detailed chronological progress in this field is presented. Special attention is given for the isobar model which is not only useful for explaining experimental data, but also important in the nuclear application. Other applications, such as in the quest of